Use of hypnotics, sedatives and anxiolytics in relation to multimorbidity in 2009-2012 - Margrét Sif Sigurðardóttir 1994- (2019)
Background: Hypnotics, sedatives and anxiolytics, used in treating insomnia, are more prescribed in Iceland than in any other Nordic country. Comparing them, the difference in the use of benzodiazepine related, Z-drugs is the most pronounced. Insomnia is often associated with chronic conditions like chronic pain and mental disorders and increases with age. Objective: The objective of this study was to analyse the use of hypnotics, sedatives and anxiolytics in multimorbid patients with different mental and chronic pain diagnoses. Methods: Data from Primary Healthcare of the Capital Area in Iceland was used in the analysis. The data covered patients seeking medical attention in the primary healthcare centres in the Capital area in the years 2009-2012. From the study population (n = 114,130) eight disease groups were created with different combination of mental and chronic pain diagnoses. The prevalence of Z-drug use and change in DDDs between years was examined. Results: The highest prevalence of three-year Z-drug use was among multimorbid patients (13.3-41.1%). The prevalence increased with each additional chronic condition and was highest among patients with at least three chronic diseases. Being comorbid with mental disorders seemed to have more effect on increased Z-drug use than being comorbid with chronic pain condition. Defined daily doses (DDDs) of Z-drugs did not increase between years for patients filling a prescription for three consecutive years. Conclusion: The prevalence of Z-drug use in multimorbid patients in Iceland is high. Even though the doses of Z-drugs did not increase between years, the majority of three-year Z-drug users in all disease groups were exceeding the recommended duration of treatment. Other treatment options for insomnia should be considered before using Z-drugs or benzodiazepine derivates long term and there should be more focus on treating underlying diseases in multimorbid patients. Bakgrunnur: Notkun svefn- og kvíðastillandi lyfja er meiri á Íslandi en á hinum ...